Peningkatan Persepsi Positif Pada Ibu Balita Melalui Kegiatan Edukasi Kesehatan Berbasis Budaya - Hartiningrum, Chanty Yunie; Apriasih, Hapi; Fitriyani, Sinta (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Objective: The purpose of this Community Service Program is to determine the increase in positive perceptions in mothers of toddlers through culture-based health education activities at the stunting locus in Singaparna District in 2024. Method: The type of research used is quantitative with a pre-experimental design method, specifically one-group-pretest-posttest design, all to assess the impact of video-based health education on mothers' perceptions in caring for toddlers. The population is mothers who have children aged 0-60 months in Cikunir Village, with purposive sampling of 57 participants. The data is presented in the form of tables, and descriptive and analytical analysis is carried out using pre-test and post-test questionnaires. The method of implementing this Community Service activity is to use health education through digital pocket book media. Result: Statistical analysis shows a significant influence between health education on mothers' perceptions, that the average value before being given education was 11.82 with the lowest value being 7 and the highest being 15. While the average value after being given health education was 13.87 with the lowest value being 10 and the highest being 15. Health education can improve the perception of mothers of toddlers about parenting patterns that prevent the risk of stunting. Conclusion: Health education using digital pocket books has a significant effect on mothers' perceptions of parenting patterns in the Sundanese tribe. Early intervention in child growth and prevention of stunting is very important to encourage infant development according to their age.